2023
DOI: 10.1002/ajh.26996
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism mortality and trends in older US adults, 2011–2019

Abstract: Venous thromboembolism (VTE) affects 1.2 million people per year in the United States. With several clinical changes in diagnosis and treatment approaches in the past decade, we evaluated contemporary post‐VTE mortality risk profiles and trends. Incident VTE cases were identified from the 2011–2019 Medicare 20% Sample, which is representative of nearly all Americans aged 65 and older. The social deprivation index was linked from public data; race/ethnicity and sex were self‐reported. The all‐cause mortality ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…[ 33 ] was based out of the Veterans Affairs health care system of which the authors acknowledge the robust access to healthcare for their cohort. When comparing our study to similar studies with disparities in access to health care, our results were consistent with the literature demonstrating worse mortality outcomes for non-White individuals [ 14 , 58 ]. Our study consisted of the highest proportion of Black individuals, helping to contribute primary literature to an underrepresented patient population.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…[ 33 ] was based out of the Veterans Affairs health care system of which the authors acknowledge the robust access to healthcare for their cohort. When comparing our study to similar studies with disparities in access to health care, our results were consistent with the literature demonstrating worse mortality outcomes for non-White individuals [ 14 , 58 ]. Our study consisted of the highest proportion of Black individuals, helping to contribute primary literature to an underrepresented patient population.…”
Section: Discussionsupporting
confidence: 91%
“…Similar results were recently published by Giorgio et al. [ 58 ] investigating a large Medicare cohort of over 125,000 individuals from 2011 to 2019. Their study demonstrated an increased 30-day (7.0 % vs 5.8%) and 1-year (40.8% vs 33.8%) mortality in Black individuals compared with White individuals with CA-VTE [ 58 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…When we analyse 1-year mortality rates in population-based studies or in other registries or databases, we observe how the 1- year mortality among PE patients varies from 19% to 52.3%. 30–32 Among the most relevant factors that could have contributed to higher mortality in our work, compared with other prospective studies that have addressed this issue, are cancer and age. The percentage of patients with cancer in previous studies ranged from 6.15% to 11%, 8 16 27 28 a figure that contrasts with the 26.7% in our series.…”
Section: Discussionmentioning
confidence: 65%
“…Venous thromboembolism (VTE), encompassing deep vein thrombosis (DVT) and pulmonary embolism (PE), presents a considerable health challenge due to its multifactorial pathogenesis and potential short- and long-term complications. Despite its potential fatality, timely and appropriate anticoagulant therapy, along with vigilant patient monitoring, has led to a gradual reduction in mortality rates, highlighting the significance of comprehensive VTE management [ 1 ].…”
Section: Introductionmentioning
confidence: 99%